Serrated polyps: innocent or guilty? - Mansilla-Vivar, Rodrigo (2021)
Serrated lesions represent a group of lesions with different genetic and biological features causing important clinical repercussions. Three types of serrated lesions are identified: hyperplastic, sessile adenomas (with and without dysplasia) and traditional serrated adenomas. Such lesions are now recognized as precancerous lesions.The carcinogenic process of serrated lesions follows a pathway including: alterations concerning activation of mitogen and protein kinase regulating the extracellular signal of other intracellular kinases (MAPK-ERK), inhibition of the apoptosis and hypermethylation of DNA and instability of microsatellites. Like for adenomatous polyps, the risk factors for serrated lesions are environmental factors, related to lifestyle and diet. The cancerogenic risk is increased by excessive alcohol consumption, obesity and poor intake of folate. When a high number of colorectal polyps with architecture serrated is diagnosed, it could be considered as serrated polyposis syndrome (SPS). According the most recent ESGE guidelines, the diagnostic criteria of the SPS, are: at least 5 polyps resected proximal to the sigmoid colon, 2 of which> 10 mm, or >20 serrated lesions of any size distributed in the entire colon. This condition presents a high risk for personal and/or familiar CRC, for this reason a regular screening colonoscopy should be performed in these patients and in their first-degree relatives.